2011
DOI: 10.1371/journal.pone.0020965
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Signal Transducer and Activator of Transcription 3 Reverses Chemotherapeutics Resistance of Leukemia Cells via Down-Regulating P-gp

Abstract: Multidrug resistance (MDR) caused by overexpression of p-glycoprotein is a major obstacle in chemotherapy of malignant cancer, which usually is characterized by constitutive activation of signal transducer and activator of transcription 3 (STAT3), but their relation between MDR and STAT3 remains unclear. Here, we showed that STAT3 was overexpressed and highly activated in adriamycin-resistant K562/A02 cells compared with its parental K562 cells. Blockade of activation of STAT3 by STAT3 decoy oligodeoxynucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 29 publications
4
69
0
Order By: Relevance
“…It is well documented that many transcription factors, such as Ap-1, NF-kB, Akt and STAT3 are involved in activation of MDR1 gene in various cancers [24,25,26,27,28,29]. STAT3 binds to the potential promoter region, +64 and +72 of MDR1 in myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that many transcription factors, such as Ap-1, NF-kB, Akt and STAT3 are involved in activation of MDR1 gene in various cancers [24,25,26,27,28,29]. STAT3 binds to the potential promoter region, +64 and +72 of MDR1 in myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…MDR1, a well-known ATP-dependent drug efflux pump, is responsible for decreased drug accumulation in multidrugresistant cells and often mediates resistance to drugs in lung and breast cancer (35)(36)(37). Inhibition of STAT3 can reverse drug resistance in leukemia (38). It has been reported that inhibiting IL-6 and EGFR signaling simultaneously results in a more effective way to control non-small-cell-lung-cancer proliferation, and inhibition of STAT3 activity can increase the sensitivity to tyrosine kinase inhibitors in head and neck cancer (39).…”
Section: Analysis Of Gene Expression In Response To the Second Wave Omentioning
confidence: 99%
“…In a recent report, the COX-2 inhibitor SC236 and the nonsteroidal antiinflammatory drug indomethacin were shown to inhibit P-gp and MRP1 expression and thus to enhance doxorubicin cytotoxicity in a MDR hepatocellular carcinoma cell line (Ye et al, 2011). Another therapeutic target in MDR leukemia may be STAT3 signaling; a recent study showed that STAT3 was overexpressed in MDR K562/AO2 leukemia cells and inhibition of STAT3 activation resulted in down-regulation of MDR1 transcription and P-gp expression (Zhang et al, 2011c).…”
Section: Downloaded Frommentioning
confidence: 99%